Assessment of phenotypic diversity of Ñuña, a local common bean (Phaseolus vulgaris L.) from the northern Andes in Peru - Santa Cruz Padilla, Angel Esteban; Vasquez Orrillo, Jorge Luis; Bardales Lozano, Ricardo Manuel; Murga Orrillo, Hipolito (Genetic Resources, 2025)
This work was supported by the Subdirección de Recursos Genéticos de la Estación Experimental Agraria Baños del Inca of the Instituto Nacional de Innovación Agraria - INIA. The authors would like to thank Armando Linares Estrada and Sebastián Llico Sánchez for their support in the field.